Pharmacognostic evaluation and antioxidant capacity of Tetracera macrophylla Hook. F. & Thoms twigs - Vera Ladeska; Berna Elya; Muhammad Hanafi; Kusmardi (GarVal Editorial Ltda., 2023)
Context: Tetracera macrophylla Hook. f. & Thoms is used empirically in traditional medicine, specifically the twig, to treat dysentery, diarrhea, diabetes, and tuberculosis symptoms. The plant contains phenolic and flavonoid compounds that offer potential as antioxidants. Aims: To evaluate the pharmacognostic characteristics of T. macrophylla, phytochemical, total phenolic and flavonoid contents, and the antioxidant capacity twig of T. macrophylla from n-hexane, ethyl acetate, and methanol extracts. Methods: Pharmacognostic evaluation was carried out by macroscopic-microscopic observation leaf and twig of the Tetracera macrophylla, and phytochemical analysis was carried out using several chemical reagents. The chromatographic profile was analyzed by thin-layer chromatography and qualitative identification of compounds by liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). The total phenolic (TPC) and flavonoid contents (TFC) were determined colorimetrically. The antioxidant capacity was determined in vitro by the FRAP and DPPH methods. Results: The microscopic analysis of leaf powder showed the presence of raphide crystals, uniseriate trichomes, and parasitic stomata, while the twig powder showed the presence of raphide crystals. The primary phenolic compounds in the active extracts were identified as 6-hydroxy-2-(2-phenylethyl) chromone, d-catechin, isorhamnetin, and epicatechin gallate. The highest TPC and TFC were found in the ethyl acetate extract. The ethyl acetate and methanol extract showed a higher antioxidant capacity than the hexane extract. The correlation matrix between TPC, TFC, and antioxidant capacity showed a robust correlation. Conclusions: The pharmacognostic evaluation of T. macrophylla revealed the presence of characteristic morphological features of the plant. A microscopic study of the leaf showed the presence of uniseriate trichomes and paracytic stomata on the abaxial epidermis. Powder analysis of twigs showed the presence of irregular starch grains, raphide crystals, and stone cells. The TPC and TFC in twigs of T. macrophylla were robustly correlated to antioxidant capacity with the FRAP method. Meanwhile, the TPC and TFC gave a moderate correlation with DPPH methods. The ethyl acetate and methanol extracts of T. macrophylla twigs showed a higher antioxidant capacity than the n-hexane extract.